Molecular characteristics of the refractory organic matter in the anaerobic and aerobic digestates of sewage sludge. Issue 58 (25th September 2018) - Li, Xiaowei; Mei, Qingqing; Yan, Xiaofang; Dong, Bin; Dai, Xiaohu; Yu, Liangliang; Wang, Yibo; Ding, Guoji; Yu, Fang; Zhou, John
Abstract : The chemical characteristics of the refractory organic matter in anaerobic and aerobic digestates are hardly known although they are significant for further improving the degradation of organic matter during sludge digestion. Abstract : The chemical characteristics of the refractory organic matter in anaerobic and aerobic digestates are hardly known although they are significant for further improving the degradation of organic matter during sludge digestion. Thus, in this study, various techniques are used to analyze the molecular properties of the total organic matter in raw sludge and mesophilic anaerobic and aerobic digestates (AnD and AoD, respectively). The results show that AnD has lower organic matter content, but the maturity and aromatization of its organic matter are lower than those of AoD. The FTIR and XPS spectra show that AoD has higher proportions of protein-like and aromatic groups and lower percentages of polysaccharide-like materials and ammonia nitrogen compared with AnD. The solid-phase fluorescence spectra indicate that AoD has a higher content of fluorescence organic matter, but its biodegradability and chemical accessibility are lower than those of AnD. Pyrolysis GC/MS analysis shows that the digestates are enriched with more lignin-like and aromatic groups and contain lower oxycompounds compared with raw sludge, especially AoD. These findings provide new insights into the molecular characteristics of the refractory organic matter in anaerobic and aerobic digestates and also provide a possible strategy to further enhance the degradation of organic matter in sewage sludge.